Understanding and Preventing Placenta-Mediated Pregnancy Complications - Skeith, Leslie; Blondon, Marc; Ní Áinle, Fionnuala (Hämostaseologie, 2020)
Placenta-mediated pregnancy complications are clinically important conditions and include preeclampsia, placental abruption, intrauterine growth restriction, and late fetal loss. Pathophysiology is complex, and may be linked to prothrombotic disorders such as antiphospholipid syndrome, whose understanding is still evolving. In this narrative review, we will present the latest evidence to better understand hemostatic mechanisms of preeclampsia, as well as in women with placenta-mediated pregnancy complications and inherited thrombophilia or antiphospholipid antibodies. Using four clinical scenarios, the mixed results of preventive efforts through the use of antithrombotic drugs (aspirin, heparin) will be discussed. We will also review knowledge gaps and ongoing research.
Keywords: pregnancy; placental complications; low-molecular-weight heparin